2005
DOI: 10.1128/jcm.43.3.1051-1058.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycobacterium Species by secA1 Sequences

Abstract: We describe a novel molecular method for the differentiation and identification of 29 mycobacterial species. The target is the secA1 gene that codes for the essential protein SecA1, a key component of the major pathway of protein secretion across the cytoplasmic membrane. A 700-bp region of the secA1 gene was amplified and sequenced from 47 American Type Culture Collection strains of 29 Mycobacterium species as well as from 59 clinical isolates. Sequence variability in the amplified segment of the secA1 gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…However, in this case, the gene was not shown to be discriminative enough for the identification of Tsukamurella spp., since the differences in the genes are minimal among the different species of the genus (Table 1) (9,10). In contrast, an analysis of a region of the secA1 gene was shown to be suitable for discrimination among four important clinical species of Tsukamurella, as it has been demonstrated for other clinically significant species of aerobic actinomycetes (12,13).…”
mentioning
confidence: 96%
“…However, in this case, the gene was not shown to be discriminative enough for the identification of Tsukamurella spp., since the differences in the genes are minimal among the different species of the genus (Table 1) (9,10). In contrast, an analysis of a region of the secA1 gene was shown to be suitable for discrimination among four important clinical species of Tsukamurella, as it has been demonstrated for other clinically significant species of aerobic actinomycetes (12,13).…”
mentioning
confidence: 96%
“…It has recently been shown that sufficient variability exists in the sequence of the secA1 gene of mycobacteria to allow discrimination of 29 species (13). We describe here a novel method of distinguishing 29 species or taxa of Nocardia, using sequence analysis of both a portion of the secA1 gene and the deduced amino acid sequence.…”
mentioning
confidence: 99%
“…Sequence analyses of the hsp65 gene (6), recA (7), SecA1 (8), DNA gyrase (9), internal transcribed spacer of the 16S-23S rRNA (10), and rpoB (11) have been attempted. Of these, analysis of the rpoB gene has been strongly recommended as a supplementary or alternative method to 16S rRNA gene analysis of mycobacteria (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%